1986
DOI: 10.1111/j.1365-2125.1986.tb03001.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiological evaluation of erosions: a quantitative method for assessing long‐term remittive therapy in rheumatoid arthritis.

Abstract: 1 The most reliable method for evaluating possible remission‐inducing properties in a drug is to measure how well it prevents the appearance of new erosions in serial X‐rays of the hands. 2 I have reviewed the literature on the development, over the last 25 years, of a standard method for quantitatively assessing the progress of erosions radiologically. 3 The only drugs thus far shown to be genuinely remission‐inducing are cyclophosphamide, high‐dose penicillamine, and (most consistently over several decades) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 69 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…At this stage of innovation, the creation of expectations by the deployment of promissory discourse and hope was certainly evident in both the United Kingdom and the United States. Some manufacturers and their research scientists even claimed in press conferences, advertisements and professional journals that their new NSAIDs promised to retard the progression of arthritic diseases, but such optimism, based on laboratory studies and minimal clinical evidence, was ultimately found to be unconvincing (Anon 1983b;Bluhm 1982;O'Brien 1986). Indeed, the newer NSAIDs came to be known as "me-too" drugs because they were distinguishable from each other only by minor molecular modifications with negligible differences in therapeutic efficacy.…”
Section: Clash and Convergence Of Expectations: Industrial Science And Regulatory Approaches To Nsaidsmentioning
confidence: 99%
“…At this stage of innovation, the creation of expectations by the deployment of promissory discourse and hope was certainly evident in both the United Kingdom and the United States. Some manufacturers and their research scientists even claimed in press conferences, advertisements and professional journals that their new NSAIDs promised to retard the progression of arthritic diseases, but such optimism, based on laboratory studies and minimal clinical evidence, was ultimately found to be unconvincing (Anon 1983b;Bluhm 1982;O'Brien 1986). Indeed, the newer NSAIDs came to be known as "me-too" drugs because they were distinguishable from each other only by minor molecular modifications with negligible differences in therapeutic efficacy.…”
Section: Clash and Convergence Of Expectations: Industrial Science And Regulatory Approaches To Nsaidsmentioning
confidence: 99%